Characterization of a novel method for the production of single‐span membrane proteins in Escherichia coli. Issue 4 (19th January 2019) - Smith, Sarah M.; Walker, Kelly L.; Jones, Alexander S.; Smith, Corinne J.; Robinson, Colin
Abstract: The large‐scale production and isolation of recombinant protein is a central element of the biotechnology industry and many of the products have proved extremely beneficial for therapeutic medicine. Escherichia coli is the microorganism of choice for the expression of heterologous proteins for therapeutic application, and a range of high‐value proteins have been targeted to the periplasm using the well characterized Sec protein export pathway. More recently, the ability of the second mainstream protein export system, the twin‐arginine translocase, to transport fully‐folded proteins into the periplasm of not only E . coli, but also other Gram‐negative bacteria, has captured the interest of the biotechnology industry. In this study, we have used a novel approach to block the export of a heterologous Tat substrate in the later stages of the export process, and thereby generate a single‐span membrane protein with the soluble domain positioned on the periplasmic side of the inner membrane. Biochemical and immuno‐electron microscopy approaches were used to investigate the export of human growth hormone by the twin‐arginine translocase, and the generation of a single‐span membrane‐embedded variant. This is the first time that a bonafide biotechnologically relevant protein has been exported by this machinery and visualized directly in this manner. The data presented here demonstrate a novel method for the production of single‐span membrane proteins in E. coli . Abstract : The large‐scale production and isolation of recombinant protein is a central element of the biotechnology industry and many of the products have proved extremely beneficial for therapeutic medicine. Escherichia coli is the microorganism of choice for the expression of heterologous proteins for therapeutic application, and a range of high‐value proteins have been targeted to the periplasm using the well‐characterized Sec protein export pathway. More recently, the ability of the second mainstream protein export system, the twin‐arginine translocase, to transport fully‐folded proteins into the periplasm of not only E . coli, but also other Gram‐negative bacteria, has captured the interest of the biotechnology industry.